Предмет: Математика,
автор: vanchen1337
(x-2)(x+2)-x(x-13) при x = -2/3
Ответы
Автор ответа:
2
Ответ:
Пошаговое объяснение:
(x-2)(x+2)-x(x-13) при x = -2/3
(x-2)(x+2)-x(x-13) = x²-4-x²+13x = -4+13x = -4-13*(2/3) = -38/3 = -12 2/3
Автор ответа:
1
Решение и ответ:
(x - 2)(x + 2) - x(x - 13), при x = -2/3
(x - 2)(x + 2) - x(x - 13) = x² - 2² - x² + 13x = x² - 4 - x²+ 13x = -4 + 13x = 13x - 4
13x - 4 = 13 · (-2/3) - 4 = -26/3 - 4 = -38/3 = -12 2/3
Для решения использовали формулу:
(a - b)(a + b) = a² - b²
Похожие вопросы
Предмет: Русский язык,
автор: margaret2233
Предмет: Русский язык,
автор: veronicalicro
Предмет: Русский язык,
автор: Saniyat3008
Предмет: Геометрия,
автор: katyatr001
Предмет: Алгебра,
автор: MemeMaster420